Multinational corporations and global production networks the implications for trade policy - Barba Navaretti, Giorgio 1960-; Haaland, Jan I. 1956-; Venables, Anthony 1953- (CEPR, 2002)
The objective of this report is to understand the role of multinational enterprises (MNEs) and production networks in economic activity. Its focus is the European Union, where MNEs account for a significant share of economic activities; it also devotes attention to the activities of US subsidiaries in Europe and of EU subsidiaries in the US, the only ones for which comprehensive data are available. There are strong arguments in favor of a new investment agreement that could coordinate foreign investment policies, but extending existing trade agreements could also do at least part of the job.
Keywords: Multinationales Unternehmen; Commercial policy; Free trade; International business enterprises; Investments, Foreign -- European Union countries; Investments, Foreign -- United States; Handelspolitik; Unternehmenskooperation; Europäische Union. Mitgliedsstaaten; USA